Is it democracy or 'democrazy'? - Abd Razak, Dzulkifli (2008)
WHEN Presidentelect-Obama picked his once bitter rival Hillary Clinton to be s high-powered Secretary of State, many voiced their reservations. Why did he do it? Could it be to scure the support of women whom he lost while campaigning against Hillary? Or could it be he needed someone attend to the hypothetical "3am call" that Hillary claimed that she is been best trained to handle?